ADAPTING THE PROFIT AND LOSS REPORT BY BUSINESS LINES IN ROMANIAN ACCOUNTING - Horia DEMIAN (Oradea Journal of Business and Economics)
In this paper we will present the creation of indicators used in the economic and financial analysis of the company based on the existing data in the company’s accounting. More precisely, we have proposed the possibility of analyzing the company’s activity on business lines, and within each business line we will have expenses and revenues distributed so that the profitability of each business line will be calculated and not only of the company’s activity as a whole. The use of such a mechanism allows us a more detailed analysis and the possibility of identifying problems more accurately when they arise. We set out to translate the Profit and Loose (P&L) report into business lines.